Relevance of necroptosis in cancer. Issue 2 (17th January 2017) - Lalaoui, Najoua; Brumatti, Gabriela
Abstract : Resistance to caspase‐dependent apoptosis is often responsible for treatment failures in cancer. Finding novel therapeutic strategies that can activate alternative cell death programs appears to be appealing. Necroptosis is a form of programmed necrosis that occurs under caspase‐deficient conditions. This alternative form of cell death has recently emerged as a potential anticancer therapy that could overcome apoptosis resistance. A growing understanding of the molecular events triggering necroptosis helped to examine its implication in cancer development and to define new therapeutic strategies. Genetic and proteomic analysis suggest that necroptosis is deregulated in many cancers. Various preclinical and clinical compounds induced necroptosis and have demonstrated significant therapeutic efficacy. Moreover, accumulating evidence has shown that necroptosis promotes anticancer immune response. A better knowledge of the cascade of events regulating necroptosis is expected to assess the feasibility of its therapeutic exploitation for cancer therapy. Abstract : The February 2017 issue contains a Special Feature on Necroptotic death signalling: evolution, mechanisms and disease relevance. In recent years, research into a genetically encoded cell death program termed necroptosis has accelerated into vogue. Many laboratories are now racing to answer key questions such as: How does it occur? When does it occur? What does it do? What is it good (or not so good) for? Answers to these will ultimately guide efforts aimed at manipulating this new pathway for therapeutic benefit. In the six articles in this ICB Special Feature, the current state of play in necroptotic cell death research is dissected in considerable detail. The articles provide timely updates on what we have learnt so far and, importantly, where we might be going. Immunology & Cell Biology thanks the coordinator of this Special Feature ‐ James Vince ‐ for his planning and input.